1997
DOI: 10.1007/bf03168559
|View full text |Cite
|
Sign up to set email alerts
|

Does intensity windowing improve the detection of simulated calcifications in dense mammograms?

Abstract: This study attempts to determine whether intensity windowing (IW) improves detection of simulated calcifications in dense mammograms. Clusters of five simulated calcifications were embedded in dense mammograms digitized at 50-1~m pixels, 12 bits deep. Film images with no windowing applied were compared with film images with nine different window widths and levels applied. A simulated cluster was embedded in a realistic background of dense breast tissue, with the position of the cluster varied. The key variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The relatively large number of cases ͑200͒ used in our study and the fact that 33% of our cases had multiple lesions also contributed to higher statistical power than earlier studies. Only two 10,16 of the seven prior studies were objective ROC studies and five [11][12][13][14][15] used very few cases ͑Յ40͒. None of the two ROC studies used optimal ROC analysis ͑e.g., DBM͒ that takes into account correlations due to the reader and case matching in the data to maximize statistical power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively large number of cases ͑200͒ used in our study and the fact that 33% of our cases had multiple lesions also contributed to higher statistical power than earlier studies. Only two 10,16 of the seven prior studies were objective ROC studies and five [11][12][13][14][15] used very few cases ͑Յ40͒. None of the two ROC studies used optimal ROC analysis ͑e.g., DBM͒ that takes into account correlations due to the reader and case matching in the data to maximize statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…10-16 and references therein͒. However, these studies are not directly applicable to modern digital mammography since one or more of the following conditions were true: the images were viewed in hard-copy mode, 10,11,[13][14][15][16] which is not the current standard as it does not take into account the flexibility of user-adjustable window and level controls in soft-copy display; the studies utilized subjective preference methods ͓i.e., non-ROC/FROC ͑free-response receiver operating characteristic͔͒ that cannot control for observer reporting threshold variability; 11,12 only effects of window-level ͑W/L͒ adjustments were studied using student observers, 13,14 whereas in practice W/L is the final step of a series of complex image processing steps performed on the raw data and radiologists are the final observers; they used in-house developed algorithms [11][12][13][14][15] rather than manufacturer-delivered algorithms, such as are used in the clinics; and none of the prior studies used modern ROC/ FROC evaluation methodology. 17,18 The aim of the current study was to determine if manufacturer-developed image processing algorithms, which are actually used under clinical conditions in a fully digital mammography reading environment at our institution, have an effect on the interpretation of digital mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, habit and experience influenced the preference of radiologists for screen-film images over processed digital images in many cases. A prior preference study (4), in which the investigators attempted to exactly match the appearance of the screen-film mammograms through MIW, showed that radiologists preferred digital mammography to screen-film imaging. Of course, such matching might not allow the full benefits of digital mammography to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…As for image quality, the accuracy of CR reading is affected by the image-processing parameters and windowing [7,8,9]. Kallergi et al [10] reported that interobserver variation in the digitized mammogram reading (105-µm pitch, 12-bit gray scale) was greater than in the film reading.…”
Section: Discussionmentioning
confidence: 98%